An investigation of the leadership experiences of principals in the government schools in Sri Lanka - Kasturi Arachchi, Chandana (My University, 2011)
School principals, like all leaders, can only be called leaders if they make a difference. In modern parlance, one frequently encounters this home spun wisdom in the statement that effective schools are led by effective principals. In the government schools in Sri Lanka principals perform leadership role as a top level manager. There are more than nine thousand government schools, and around same number of principals are employed in those schools in Sri Lanka (Central Bank Report in Sri Lanka, 2010). It seems that the successfulness of principals as effective leaders depends on their background, experience, qualifications, capacities and leadership practices that they applies. Principals’ leadership role is very influential in order to achieve mission and objectives of any school. Therefore it is very significant to explore their perceptions on school leadership in order to understand the real situation in the government schools in Sri Lanka. This study explored educational leadership experiences of principals working in the Colombo district 1AB public schools in Sri Lanka. While much research has been carried out on school effective principalship, very little has been undertaken in Sri Lanka. As such, we know very little about school principal’s experiences in effective educational leadership in Sri Lanka. The Sri Lankan Ministry of Education, various educational authorities and school principals could potentially benefit from this study. The information will be able to use by the principals to support their leadership journey. The specific focus of this research design had emerged out of the following questions: What constitutes of effective principalship in government schools? What issues prevent the principals from being effective in leading their schools? What is the nature of educational leadership experiences of principals? This study specifically aimed to investigate; educational leadership experiences of principals, challenges faced by school principals as leaders. This study is in the nature of an interpretive paradigm, and qualitative research method was employed. Research data was gathered using semi-structured interviews conducted with ten principals. In this study, schools were selected using random sampling technique, and all the principals in the selected schools purposively chosen for gathering information. The interviews were recorded, transcribed, and in order to analyse data in this study thematic analytical approach was adopted. Thematic analysis focuses on identifiable themes and patterns of living and/or behaviour of people. Thematic analysis is commonly used by researchers and in particular is suitable for analyzing and reporting personal qualitative interview data (Mutch, 2005). Therefore, it was employed thematic analytical approach since it is more appropriate to analyse qualitative data in this study. Many scholars suggest that the strategies for becoming an effective leader. Tschanen-Moran (2004) proposed several strategies to become an effective leader as: exercising personal presence, active listening, powerful questioning, creation of awareness, planning and goal setting, design of actions, management of progress and accountability. Show (2007) suggested that an effective leader: has vision, is strategic, is self confident and able to inspire confidence in others, is trustworthy and credible, has good communication skills, is able to motivate and influence others, has ability to foster teamwork, collaboration and partnership, is continually developing themselves and also encourages development in others. Finkelman (2006) suggested for leaders to be effective as change agents they need to do more than just understand, accept and manage change. During a change process empowerment can become an important factor. Fullan (2003) said that effective leaders know that reculturing is the key to progress but they also understand that it is hard work. Scholars are explicit in emphasizing the fact that for any school to be successful, it must be lead by an extremely effective principal. The participants perceived modeling as the most effective way of leading; they believed that actions speak louder than words. Moreover they supposed that to be an effective leader, one needs to manage one self, before being able to manage others and direct them to success. The participants suggested that being knowledgeable in policy, current rules and regulations and current practice are essential contributors to very effective school principalship. One principal stated his ideas about school leadership: ‘if school principal ready to work hard for the development of school, and there is a visible leadership, it will be able to get maximum contribution of staff and community members for school development’. Principal must have deep attention in leading the school, and shows great enthusiasm towards the process. School principals should motivate staff to grow. The participant believed that a more passionate and concerned principal would be more successful in leading to transform the school, and motivate the staff to perform to the best of their abilities, ultimately to the final benefit of the students. It is very important for a school principal to develop a vision, mission for the school and set the direction or course for the school with a well defined and achievable set of goals (Ministry of Education, 2008). Majority of the principal participants said that: ‘the recognition of the community is very important to be an effective leader. In addition, to be a good leader and to get recognition, principal should have experiences, qualifications and training, and he/she must have good attitudes towards the school, staff and students development’. The participants mention the importance of the principal being knowledgeable about the concepts of management and strengthen in those skills. Moreover, they suggested that the principals to have a thorough knowledge of current educational and leadership theories. School principals must be innovative, creative and business-minded to generate funds for school development, even though it is not a central part of their educational roles. The principals participated in this study indicated that for one to be an effective leader must have leadership qualities. Some of these leadership qualities are skills in organizing, being visionary, being respectful, honesty, humility, firmness and making the right and correct decisions. It has been noted that some school leaders were usually late in getting to school and leave earlier than the rest of the teachers. The foremost issue to be addressed by the government was a training package for all aspiring and newly appointed school principals. They claimed that there is no appropriate pre-principalship training or professional development packages. According to the participants in this study, there was no pre-principalship professional development opportunities for all aspiring leaders, so there was no in-service professional training and development opportunities for serving principals to review, upgrade or otherwise improve their knowledge base. The lack of positive and timely response from the Ministry of Education and education authorities in Sri Lanka on significant issues affected the smooth and efficient and effective administration of the schools. The principals felt disempowered by the organizational gap that exists between the Ministry of Education and the schools. They felt powerless to assist their school or the staff and students. Inadequate financial and other resources were impediment to effective principalship. According to the participants’ views, the Ministry of Education did not provide sufficient funds adequately to finance all schools. Since schools did not have enough financial strength, they had a responsibility to generate funds to fulfill their financial requirements. It seemed that most of the schools depend on the funds provided by the Ministry, and did not pay their attention for organizing fund raising activities at school level. It is recommended that to conduct programmes; pre-principal training and support for ongoing professional training, and collegial learning opportunities for serving principals; providing positive and timely responses to the school principals’ enquiry and requests from the Ministry of Education and Education authorities; in addition, providing adequate human resources for the schools in time by the relevant authorities for enabling principals to manage their school effectively since they do not have power and authority to recruit staff. It should be empowered principals to face challenges in leading school. For instance, they must be skilled for organizing funds raising activities at school level to meet financial and other essential requirements of the school without depending on the ministry of Education. Therefore principals must be developed entrepreneur skills to be a successful leader.